The professional secretary's handbook - George, Peter (Lagos, Nigeria Businees Publishing Company Limited, 1993)
This book highlights some of the basic administrative tips and tricks to improve the productivity and effectiveness of the secretaries
Includes bibliographical references
mf 23/01/2019
Ref.
Keywords: Secretarial services; Office practice; Secretaries